Pneumococcal serotypes in adult non-invasive and invasive pneumonia in relation to child contact and child vaccination status. Issue 2 (18th September 2013) - Rodrigo, Chamira; Bewick, Thomas; Sheppard, Carmen; Greenwood, Sonia; MacGregor, Vanessa; Trotter, Caroline; Slack, Mary; George, Robert; Lim, Wei Shen
Abstract : Background: On a population level, pneumococcal conjugate vaccination in children has reduced the incidence of vaccine-type disease in all age groups, including older adults. Few individual level studies have been performed describing the pneumococcal serotypes associated with adult community acquired pneumonia (CAP) and quantifying associations with child contact and child vaccination status. Methods: Pneumococcal serotypes were determined using a validated multiplex immunoassay (Bio-Plex) in a large prospective cohort of adults hospitalised with CAP. Child (<16 years old) contact history and child pneumococcal vaccination status were obtained from patients and public health records, respectively. Results: Of 1130 participants, 329 (29.1%) reported child contact, and pneumococcal infection was identified in 410 (36.3%). Pneumococcal CAP was commoner in adults with child contact (148/329 (45.0%) vs 262/801 (32.7%); adjusted OR 1.63, CI 1.25 to 2.14; p<0.001). A serotype was determined in 263 of 410 (64.1%) adults with pneumococcal CAP; 112 (42.6%) reported child contact, 38 (33.9%) with a vaccinated child. Adults in contact with a vaccinated child were significantly less likely to have vaccine-type CAP compared with adults in contact with an unvaccinated child (6 of 38 (15.8%) vs 25 of 74 (33.8%), respectively; OR 0.37, 95% CI 0.14 to 0.99; p=0.044). Conclusions: Pneumococcal aetiology in adult CAP is independently associated with child contact and implicated serotypes are influenced by child vaccination status. This is the first study to demonstrate these associations at an individual rather than population level; it affirms that 'herd protection' from childhood vaccination extends beyond adult invasive disease to pneumococcal CAP.